An exploration of migrant women's perceptions of public health messages to reduce stillbirth in the UK: a qualitative study - Tomasina Stacey; Melanie Haith-Cooper; Nisa Almas; Charlotte Kenyon (BMC, 2021)
Abstract Background Stillbirth is a global public health priority. Within the United Kingdom, perinatal mortality disproportionately impacts Black, Asian and minority ethnic women, and in particular migrant women. Although the explanation for this remains unclear, it is thought to be multidimensional. Improving perinatal mortality is reliant upon raising awareness of stillbirth and its associated risk factors, as well as improving maternity services. The aim of this study was to explore migrant women's awareness of health messages to reduce stillbirth risk, and how key public health messages can be made more accessible. Method Two semi-structured focus groups and 13 one to one interviews were completed with a purposive sample of 30 migrant women from 18 countries and across 4 NHS Trusts. Results Participants provided an account of their general awareness of stillbirth and recollection of the advice they had been given to reduce the risk of stillbirth both before and during pregnancy. They also suggested approaches to how key messages might be more effectively communicated to migrant women. Conclusions Our study highlights the complexity of discussing stillbirth during pregnancy. The women in this study were found to receive a wide range of advice from family and friends as well as health professionals about how to keep their baby safe in pregnancy, they recommended the development of a range of resources to provide clear and consistent messages. Health professionals, in particular midwives who have developed a trusting relationship with the women will be key to ensuring that public health messages relating to stillbirth reduction are accessible to culturally and linguistically diverse communities.